Analysis and simulation of BECCS vertical integration model in China based on evolutionary game and system dynamics. (1st August 2022) - Guo, Jian; Zhong, Minghao; Chen, Shuran
Abstract: Bioenergy with carbon capture and storage (BECCS) is a key negative emission technology in response to climate change. The industrial chain of BECCS is composed of multi-agent participants: farmers, middlemen, enterprises. This paper fills a gap in BECCS research by establishing a tripartite evolutionary game model and conducting system dynamics simulation to analyze the participants' interaction and strategy choices on system equilibrium in supply chain of BECCS under vertical integration operation model, and further discussing the influence of policy incentives on BECCS. The results show that the willingness of both enterprises and middlemen participate in the cooperation is very low under current scenario. Therefore, appropriate incentives must be taken to promote commercial deployment of BECCS. From sensitivity analysis, the following useful references for practical applications of BECCS in the future are obtained: Compared with other factors, costs of carbon storage have a more significant impact on the evolutionary trajectories and are highly sensitive to evolutionary equilibrium. The government should subsidize carbon utilization and electricity tariffs, but could not provide an initial investment subsidy for BECCS retrofit. Vigorously developing middlemen and promoting the improvement of carbon trading market and carbon tax policies are also of great significance to implementation of BECCS. Highlights: We analyze Bioenergy with carbon capture and storage in vertical integration model. The industrial chain of BECCS is composed of farmers, middlemen, enterprises. A tripartite evolutionary game model is built to analyze multi-agent interaction. Willingness of players participate in cooperation is low under current scenario. Appropriate incentives must be taken to promote the deployment of BECCS.